Exploring Language Style Use in The Novel Small Things Like These by Claire Keegan - Fita Khusna Lufia; S., Nurhayati (Universitas Nasional, 2025)
Language in literary works serves not only as a tool for conveying messages and storytelling, but also as a medium of representation (a symbolic space) that shapes the identities of characters, social relations, and narrative dynamics. This research aims to analyse language styles used by the characters in Small Things Like These, a novel by Claire Keegan. The analysis is based on the five language styles proposed by Martin Joos: Frozen Style, Formal Style, Consultative Style, Casual Style, and Intimate Style. In addition, the researcher employs Janet Holmes”s theory to investigate how social factors, including participants, setting, topic, and function, influence the language styles chosen by the characters. This research employed a qualitative descriptive method. The data were collected by reading the novel and identifying utterances that reflect specific language styles. The researcher focused on conversations that illustrate shifts in style due to social relationships and emotional context. The findings show that all five language styles appear, with Casual Style being the most dominant (111), followed by Intimate (22), Consultative (17), Formal (11), and Frozen (4). These variations reflect the influence of social roles, emotional distance, power, and solidarity throughout the narrative, and depend on the language”s formality.